Ontime Application System Analysis - Dahlan, Dahlan; Riyandi, Albert (Adpebi International Journal of Multidisciplinary Sciences, 2024)
Employee absenteeism is a very crucial aspect in an institution. Employee discipline can be seen from attendance at both private and government offices. The South Tangerang City DPRD Secretariat Office is one of the Government Agencies that applies employee attendance as a basis for assessing compliance with regulations. In its implementation, taking employee attendance already uses Android-based online attendance called Ontime, Ontime Based Online is an online (Mobile) based attendance application Apps) but there are still several problems in using it, one of which is that there are still bugs in using this application, so it is not yet known whether the status of using this online attendance is at a satisfactory level or not. Therefore, research on user satisfaction needs to be carried out to measure how satisfied users are with this online attendance application. This research uses quantitative methods with the webqual 4.0 model. The data collection technique is carried out in two ways, namely interviews and questionnaires, processing data analysis using IBM SPSS Statistics. With the mean result of user satisfaction being 87.2% in the "very good" categoryKeywords: User Satisfaction, Online Attendance, Webqual